2022
DOI: 10.1186/s12887-022-03255-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of mid-regional pro-Adrenomedullin as a biomarker of invasive bacterial infection in children: a systematic review

Abstract: Background Invasive bacterial infections (IBI) in children present a difficult clinical challenge. They are often life-threatening, however in the early stages they can be hard to differentiate from benign viral infections. This leaves clinicians with the risk of missing a serious IBI diagnosis or inappropriately using antimicrobials in a child with a viral infection- contributing to the ongoing development of increased antimicrobial resistance. Hence, biomarkers which could aid in early detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Other studies also yielded similar results [ 86 , 87 ]. Recently, a meta-analysis suggested that MR-proADM testing alone is poor at identifying invasive bacterial infections in young children [ 88 ], which may be related to the population under study, the measurement time and other factors. In addition, it may be more meaningful to determine the time trend of MR-proADM levels in septic patients with pulmonary infection [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also yielded similar results [ 86 , 87 ]. Recently, a meta-analysis suggested that MR-proADM testing alone is poor at identifying invasive bacterial infections in young children [ 88 ], which may be related to the population under study, the measurement time and other factors. In addition, it may be more meaningful to determine the time trend of MR-proADM levels in septic patients with pulmonary infection [ 77 ].…”
Section: Discussionmentioning
confidence: 99%